Clinical Pregnancy After Elimination of Embryo Fragments Before Fresh Cleavage-stage Embryo Transfer - Luis Humberto Sordia-Hernandez; Felipe Arturo Morales Martinez; Lorna Marissa Frazer Moreira; Lilith Villarreal Pineda; Maria Ofelia Sordia-Piñeyro; Otto Hugo Valdes Martinez (Tehran University of Medical Sciences, 2020)
Objective: To determine if the elimination of fragments in cleavage-stage embryos, before fresh transfer, improves pregnancy rates in in vitro fertilization cycles. Materials and methods: This is a Prospective observational case-control study carried out at a University Reproductive Center. We included Twenty-six infertile patients divided into two groups. Group one: 13 patients with embryos classified as grade B and C (embryos with fragments) according to the Hill classification, and Group two: 13 patients with grade A embryos (embryos with no fragments). Embryo Defragmentation was performed in embryos of group one 65 to 68 hours after conventional fertilization. Fresh embryo transfer was made after two hours post fragments removal. Reproductive results were evaluated and compared between both groups. Results: The total number of clinical pregnancies was nine. In group one there were 5 (38.5 %); in group two, there were 4 (30.8%). The difference was not statistically significant (p = 0.68). Two abortions were reported in the study, both in group one; were fragment elimination was performed. This represents an abortion rate of 40% in patients who got pregnant in this group. These patients had twice the probability of suffering an abortion (OR 2.1; 95% CI 1.4-3.37). Ongoing pregnancies were similar in both groups. Conclusion: Removal of fragments in freshly transferred day three embryos could be an alternative to increase clinical pregnancy and ongoing pregnancy rates in patients who have only poor-quality embryos. Despite the relationship with a higher abortion rate, this strategy could represent a real alternative for this type of patient.